The role of advanced oxidation processes in drinking water treatment - Philippe, Karine K. (Cranfield University, 2010)
Removal of natural organic matter (NOM) is an ever growing challenge for water utilities as many surface waters used for drinking water in the UK exhibit increasing organics levels and it is well known that these organics can lead to problems such as water colouration, unpleasant odour and taste, bacterial growth and disinfection by-products (DBPs) formation. NOM is traditionally removed by coagulation, however in the case of hydrophilic organic matter rich waters the performances of these processes are not able to remove sufficient organic matter leading to potential failures of DBP regulations. Here two advanced oxidation processes (AOPs) UV/H2O2 and TiO2 photocatalytic oxidation were studied to investigate how they could be integrated in a drinking water flowsheet to meet this challenge. Substantial structural changes in the organic matter were observed: loss of aromaticity and double bonded character, shift towards lower molecular weight (MW) more hydrophilic compounds and formation of oxygenated by-products. Although hydrophobic rich waters seem more suitable to AOP treatment as preferential attack of high MW hydrophobic compounds was demonstrated, no correlation was found between physical properties of nine NOM surrogates and removal by UV/TiO2. Dark adsorption onto TiO2 was shown to remove preferentially high molecular weight hydrophobic anionic compound such as tannic acid. UV/H2O2 combined with coagulation did not show any significant benefits in NOM removal as UV/H2O2 appeared to target similar components as coagulation (high MW, hydrophobic and charged) and to form by-products recalcitrant to coagulation. The combination of both AOPs with fresh GAC showed moderate benefits in Abstract ii trihalomethane formation potential (THMFP) and non purgeable organic carbon (NPOC) removal highlighting the role of size and surface chemistry on adsorption onto GAC. Biodegradability of the water did not exhibit any significant change after both AOP treatments within the studied conditions possibly due to insufficient UV irradiation and presence of organics recalcitrant to biodegradation.